A new Acrulia species from Danish amber: (Coleoptera: Staphylinidae: Omaliinae: Omaliini) - Shavrin, Alexey V.; Solodovnikov, Alexey; Kairišs, Kristaps; Shaw, Josh Jenkins (Historical biology, 2023)
Acrulia danica Shavrin sp. n. from late Eocene Danish amber is described and illustrated based on a female holotype. The new species, embedded within a small piece of amber, was scanned using X-ray micro-computed tomography (mu CT), to enable the detailed study of its morphology including the taxonomically important structure of the accessory sclerite. Previously, only three extant species of the genus Acrulia Thomson, 1858 were known from the Palaearctic Region. The new species is compared with extant congeners and the importance of a detailed study of the fossil entomofauna of the Danish amber is discussed in view of the hypotheses about its different origin from other European ambers.